Lack of phenological shift leads to increased camouflage mismatch in mountain hares - Zimova, Marketa (Dryad, 2020)
Understanding whether organisms will be able to adapt to human-induced
stressors currently endangering their existence is an urgent priority.
Globally, multiple species moult from a dark summer to white winter coat
to maintain camouflage against snowy landscapes. Decreasing snow cover
duration due to climate change is increasing mismatch in seasonal
camouflage. To directly test for adaptive responses to recent changes in
snow cover, we repeated historical (1950s) field studies of moult
phenology in mountain hares (Lepus timidus) in Scotland. We found little
evidence that population moult phenology has shifted to align seasonal
coat colour with shorter snow seasons, or that phenotypic plasticity
prevented increases in camouflage mismatch. The lack of responses resulted
in 35 additional days of mismatch between 1950 and 2016. We emphasize the
potential role of weak directional selection pressure and low genetic
variability in shaping the scope for adaptive responses to anthropogenic
stressors.